Rancang Bangun Internet of Things (IoT) Pengaturan Kelembaban Tanah untuk Tanaman Berbasis Mikrokontroler - Puji Ariyanto; Agus Iskandar; Ucuk Darusalam (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Soil moisture is needed in rice fields for plant growth, with attention to soil moisture in rice fields, it can increase fertility in the land which impacts existing plants. But in regulating soil moisture requires a level that is following the existing plants, because each plant has different humidity settings. This research will design a tool to adjust soil moisture in rice fields automatically to maintain soil moisture according to plant needs. This tool is designed to use a Soil Moisture sensor which can later be used as input data to the ESP8266 to drive a Servo Motor as a soil moisture regulator, a Servo Motor as an irrigation door drive. In making the design of irrigation arrangements, moisture data from each plant is needed because each plant has a different moisture content, from the results of the study, it was found that the soil moisture of kale plants was Â± 49% - 68%, and soil moisture of corn plants ± 48% - 63%.